COMMUNITY EMPOWERMENT FOR PHYSICAL DISABILITIES THROUGH THE INDEPENDENT GROWING FARMERS GROUP (TUMAN) DPC-PPDI CIMAHI CITY - Komarudin, Danti; Yuningsih, Yuyun (Journal of Economic Empowerment Strategy (JEES), 2025)
Study This entitled " Community Empowerment for People with Disabilities " Disability Through Growing Farmers Group Independent (TUMAN) DPC-PPDI Cimahi City "and aims to For explain how is the empowerment process public for sufferer disabilities who want to develop potential they in field agriculture . One of the efforts made is with join in Growing Farmers Group Mandiri (TUMAN), which was formed directly by the Board of Directors of the Cimahi City Branch of the Indonesian Disabled Association. In the research this , is used method qualitative with approach studies case For dig information more deep regarding the empowerment process said . The selection informant done with use purposive sampling technique , where informants are selected is those who have involvement direct in group “TUMAN” farming . As for the technique data collection was carried out through observation , interviews , and studies documentation obtained from results observation directly in the group farmer . Research results show that empowerment public in context This Empowerment public in study This aiming For increase independence sufferer disability , so that they can fulfil need base in a way independent without must always depend on others. Through involvement in Growing Farmers Group Independent (TUMAN), the people with disabilities disability given chance For develop skills in the field agriculture , such as technique match planting, management land, as well as marketing results agriculture existence skills this, they No only to obtain income yourself, but also build a sense of trust self and awareness will potential that is owned. In addition, empowerment This also provides access to various source Power productive so that they can follow participate in development social as well as involved in the process of taking decision. With existence empowerment this , the bearer disability can to obtain skills in field agriculture , improving level live , and expand chance more economy Good.